Mobile Robot Navigation Functions Tuned by Sensor Readings in Partially Known Environments - Loizou, Savvas; Rimon, Elon D. (My University, 2022)
Mobile robot navigation functions provide geometric path planning that can be used to control the physical mobile robot system. This letter extends the theory of mobile robot navigation functions to planar environments populated by unknown obstacles. The robot has knowledge of the environment outer boundary but must use an obstacle sensor with sector-shape footprint during navigation. The letter introduces on-line tuning of navigation functions based on sensor readings of obstacles and the robot state upon detection of new obstacles in the environment. The letter describes a feedback control law that changes its structure according to the current navigation function, with trajectory damping that ensures smooth monotonic approach to the target. The correctness of the navigation controller in terms of obstacle avoidance and arrival to the target is established. In addition to the analytic guarantees, simulation studies describe the robot system state parameters during navigation in an office floor environment populated by unknown obstacles.
Keywords: Collision avoidance; Motion and path planning; Reactive and sensor-based planning